2018
DOI: 10.1111/odi.12989
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MAPK/ERK pathway proteins and KRAS mutations in adenomatoid odontogenic tumors

Abstract: Objective This study aimed to assess the frequency of KRAS mutation and its association with the presence of the MAPK/ERK signaling pathway proteins in adenomatoid odontogenic tumors. Study Design Paraffin‐embedded tissue samples from nine cases of adenomatoid odontogenic tumor were used. Genomic DNA was extracted from each sample; in one case, genetic mutations in 50 cancer‐associated genes were examined by next‐generation sequencing. Hotspot mutations in the RAS family were analyzed by Luminex assay using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
3
17
0
1
Order By: Relevance
“…Interestingly, the proportion of AOTs with KRAS driver mutation, is similar to the proportion of driver mutations reported in ameloblastoma. Due to its high frequency, KRAS mutations were proposed as a driver mutation and signature marker of AOTs [22][23][24]. Because KRAS mutations are a recurrent finding in AOTs, Coura et al [22], suggested the presence of KRAS G12V/R to help in the diagnosis of controversial cases of AOT, in the same way that BRAF V600E could be used in routine ameloblastoma diagnostics [14,38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the proportion of AOTs with KRAS driver mutation, is similar to the proportion of driver mutations reported in ameloblastoma. Due to its high frequency, KRAS mutations were proposed as a driver mutation and signature marker of AOTs [22][23][24]. Because KRAS mutations are a recurrent finding in AOTs, Coura et al [22], suggested the presence of KRAS G12V/R to help in the diagnosis of controversial cases of AOT, in the same way that BRAF V600E could be used in routine ameloblastoma diagnostics [14,38].…”
Section: Discussionmentioning
confidence: 99%
“…Six articles reported mutations in AOT [4,[22][23][24][25][26]. A total of 59 AOTs were assessed under different genomic techniques, such as direct sequencing, targeted NGS panels, and TaqMan allele-specific qPCR (Table 1).…”
Section: Gene Mutationsmentioning
confidence: 99%
See 3 more Smart Citations